XAS Corroboration of the Uptake and Storage of CeO(2) Nanoparticles and Assessment of their Differential Toxicity in Four Edible Plant Species - López-Moreno, Martha L. (2010)
Fate, transport, and possible toxicity of cerium oxide nanoparticles (nanoceria, CeO(2)) are still unknown. In this study, seeds of alfalfa (Medicago sativa), corn (Zea mays), cucumber (Cucumis sativus), and tomato (Lycopersicon esculentum) were treated with nanoceria at 0–4000 mg L(−1). Cerium uptake and oxidation state within tissues were determined using ICP-OES and XAS, respectively. Germination rate and root elongation were also determined. Results showed that nanoceria significantly reduced corn germination (about 30% at 2000 mg L(−1), p < 0.05), and at 2000 mg L(−1) germination of tomato and cucumber was reduced by 30% and 20%, respectively (p < 0.05). Root growth was significantly promoted (p < 0.05) by nanoceria in cucumber and corn but reduced (p < 0.05) in alfalfa and tomato. Almost at all concentrations nanoceria promoted shoot elongation in the four plant species. XAS data clearly showed the nanoceria within tissues of the four plant species. To the authors’ knowledge, this is the first report on the presence nanoceria within plants.